Security and Privacy in Mobile Information and Communication Systems Second International ICST Conference, MobiSec 2010, Catania, Sicily, Italy, May 27-28, 2010, Revised Selected Papers - Schmidt, Andreas U.; Russello, Giovanni; Lioy, Antonio; Prasad, Neeli R.; Lian, Shiguo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
MobiSec 2010 was the second ICST conference on security and privacy in mobile information and communication systems. With the vast area of mobile technology research and application, the intention behind the creation of MobiSec was to make a small, but unique contribution to build a bridge between top-level research and large scale application of novel kinds of information security for mobile devices and communication.
Session 1: Identity and Privacy I -- Personalized Mobile Services with Lightweight Security in a Sports Association -- User Authentication for Online Applications Using a USB-Based Trust Device -- XtreemOS-MD SSO -- Session 2: Identity and Privacy II -- A Mobile and Reliable Anonymous ePoll Infrastructure -- Enhancing Privacy-Preserving Access Control for Pervasive Computing Environments -- Session 3: Location and Tracking -- Algorithms for Advanced Clandestine Tracking in Short-Range Ad Hoc Networks -- A Privacy-Enabled Architecture for Location-Based Services -- A Novel Scheme for Supporting Location Authentication of Mobile Nodes -- Session 4: Ubiquitous Security -- Optimized Resource Access Control in Shared Sensor Networks -- Secure Distribution of the Device Identity in Mobile Access Network -- Network Resilience in Low-Resource Mobile Wireless Sensor Networks -- Session 5: Devices -- An Analysis of the iKee.B iPhone Botnet -- Event-Based Method for Detecting Trojan Horses in Mobile Devices -- AES Data Encryption in a ZigBee Network: Software or Hardware?.
Keywords: Computer science; Computer Communication Networks; Data encryption (Computer science).; Computer software; Information systems; Information Systems; Computer Science; Computer Communication Networks; Management of Computing and Information Systems; Data Encryption; Algorithm Analysis and Problem Complexity; Information Systems Applications (incl.Internet).; Computers and Society